2010
DOI: 10.1111/j.1600-0714.2010.00989.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of systemic eradication therapy against oral Helicobacter pylori

Abstract: Almost half of the patients with gastric H. pylori harbored the bacterium in the oral cavity. After the eradication therapy, H. pylori was not detected in the oral cavity, what suggests high effectiveness of the therapy protocol in the oral cavity, or it is possible that oral H. pylori is of a transient character.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
(44 reference statements)
1
13
0
1
Order By: Relevance
“…An interesting study by Bago et al [55] involved 56 patients with UBT-proven H. pylori infection, and 41.1% of patients harbored the bacterium in oral cavity, as detected by PCR. Three months after the triple eradication therapy (PPI twice daily/amoxicillin/clarithromycin), the eradication rate in stomach was 78.3%, and surprisingly, H. pylori was not detected in any sample from oral cavity.…”
Section: Ophthalmology Skin and Oral Mucosa Diseasesmentioning
confidence: 99%
“…An interesting study by Bago et al [55] involved 56 patients with UBT-proven H. pylori infection, and 41.1% of patients harbored the bacterium in oral cavity, as detected by PCR. Three months after the triple eradication therapy (PPI twice daily/amoxicillin/clarithromycin), the eradication rate in stomach was 78.3%, and surprisingly, H. pylori was not detected in any sample from oral cavity.…”
Section: Ophthalmology Skin and Oral Mucosa Diseasesmentioning
confidence: 99%
“…Most published studies have aimed to investigate the oral cavity as a source for subsequent gastric infections, which, of course, is an important issue in this field of research (Namiot et al, 2010;Chaudhry et al, 2011;Silva et al, 2010;de Souza Gonçalves et al, 2009;Bago et al, 2011;Eskandari et al, 2010). In contrast to the results presented here, many studies clearly reported the occurrence of H. pylori in dental plaque and concluded that there was an association between gastroesophageal disease and dental oral status (Silva et al, 2009(Silva et al, , 2010; Morales-Espinosa et al, …”
Section: Discussionmentioning
confidence: 60%
“…Присутствие Helicobacter pylori в ротовой поло-сти рассматривают как источник реинфекции сли-зистой оболочки желудка у больных с гастродуоде-нальной патологией после эрадикационной терапии [4,5], так как полость рта является перманентным резервуаром для персистирования Helicobacter pylori [2]. При лечении КПЛ СОР одним из основных эта-пов комплексной терапии, помимо общей терапии, является местное консервативное лечение.…”
Section: Abstract: Lichen Ruber Planus Oral Cavity Mucosa Helicobaunclassified